Transformation of Sharia Supervision in the Digital Era: Challenges and Opportunities - Edy Saputra; Mohammad Ridwan; Hamdanil Hamdanil; Zhilwan Tahir Hama Faraj (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to explore the transformation of Shariah supervision in the digital era, as well as to identify the challenges and opportunities arising from the adoption of technology in the Islamic finance sector. Using a qualitative descriptive method and content analysis of relevant literature, the study finds that digitalization offers significant opportunities to enhance transparency and the efficiency of Shariah supervision through technologies such as blockchain and artificial intelligence (AI). These technologies enable faster, more accurate, and automated transaction monitoring. However, significant challenges arise, particularly in terms of global regulation, differing interpretations of Shariah principles across countries, and limited technological literacy among members of the Shariah Supervisory Board (SSB). Therefore, the digital transformation of Shariah supervision requires collaboration between regulators, Islamic financial institutions, and the religious scholar community to develop a comprehensive regulatory framework. Additionally, enhancing technological literacy for SSB members is crucial to enable them to conduct supervision that is responsive to the rapid advancements in digital technology. This study contributes new insights by proposing the adoption of digital technologies that can improve the efficiency and transparency of Shariah supervision, while also addressing existing challenges in regulation and Shariah interpretation. Suggestions for future research include further exploration of the implementation of global regulatory standards that can be accepted by countries with differing interpretations of Shariah principles, as well as examining the impact of technological literacy on the quality of supervision carried out by the SSB.